2020
DOI: 10.1021/acs.biochem.0c00081
|View full text |Cite
|
Sign up to set email alerts
|

Protein Farnesyltransferase Catalyzes Unanticipated Farnesylation and Geranylgeranylation of Shortened Target Sequences

Abstract: Protein prenylation is a posttranslational modification involving the attachment of a C15 or C20 isoprenoid group to a cysteine residue near the C-terminus of the target substrate by protein farnesyltransferase (FTase) or protein geranylgeranyltransferase type I (GGTase-I), respectively. Both of these protein prenyltransferases recognize a C-terminal "CaaX" sequence in their protein substrates, but recent studies in yeast-and mammalian-based systems have demonstrated FTase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…The differences in the prenylated proteins identified may be attributed to the differences in the cell line employed, labeling conditions, the enzymatic parameters associated with the probe used or the specific MS instrumentation employed for analysis. While extended C(X) 3 X-box containing proteins and Cxx peptides have been demonstrated to be in vitro prenylation substrates 5 , 6 , none of those proteins were found to be enriched in a statistically significant manner in our analysis. Several of these polypeptides do exist in mammalian proteomes, however their endogenous levels or efficiency of prenylation may be too low to be detected using the current chemical proteomic strategies.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The differences in the prenylated proteins identified may be attributed to the differences in the cell line employed, labeling conditions, the enzymatic parameters associated with the probe used or the specific MS instrumentation employed for analysis. While extended C(X) 3 X-box containing proteins and Cxx peptides have been demonstrated to be in vitro prenylation substrates 5 , 6 , none of those proteins were found to be enriched in a statistically significant manner in our analysis. Several of these polypeptides do exist in mammalian proteomes, however their endogenous levels or efficiency of prenylation may be too low to be detected using the current chemical proteomic strategies.…”
Section: Discussionmentioning
confidence: 54%
“…1 A) 3 , 4 . Interestingly, recent studies have shown that extended C(X) 3 X motifs in model proteins can be farnesylated within cells 5 , while shortened Cxx peptides are also acceptable FTase substrates in vitro 6 . Dual geranylgeranylation on a family of Rab proteins also occurs on C-terminal CCXX, CXC, or CC motifs catalyzed by rab geranylgeranyltransferase (GGTase-II or RabGGTase) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The yeast strains used in this study have been previously described ( Table S5 ) [ 30 ]. Yeast strains were propagated at rt in either YPD or appropriate selective media when plasmid transformed.…”
Section: Methodsmentioning
confidence: 99%
“…140,141 Recent efforts to expand the existing accepted paradigm of protein S-prenylation have shown that proteins terminating in longer (CXXXX) or shorter (CXX) C-terminal motifs can be efficiently modified by the prenyltransferase enzymes. 142,143 Although these sequences have been shown to be substrates in vitro and within cells, there is no reported evidence of these types of modifications on endogenous proteins to date. Singly prenylated proteins often undergo additional processing steps to increase their hydrophobicity.…”
Section: S-prenylationmentioning
confidence: 99%
“…In addition, the same group reported that peptide models with shortened CXX sequences can also be recognized as S-prenylation substrates in vitro. 143 These studies highlight the promiscuity of prenyltransferase enzymes, and may expand our current understanding of their substrate recognition and potentially enlarge the scope of S-prenylation substrates. However, it has been noted that no endogenous proteins terminating in such unconventional prenylation motifs have been identified.…”
Section: S-prenylation Substratesmentioning
confidence: 99%